NSAIDs and Triptans – a (not) New Treatment Option for Migraine - Kakta, B.; Mameniškienė, Rasa (Neurologijos seminarai, 2023)
Every day, around 7% of population will experience headache caused by migraine. Migraine is one of the leading causes of years lived with disability, and it also causes significant negative economic impact, as most as the affected population is of working age. Pathogenesis of migraine includes neurogenic inflammation, which, in turn, causes peripheral sensitization of trigeminal nerve mechanoreceptors. As peripheral sensitization lingers on, central sensitization of the spinal trigeminal nucleus occurs. Non-steroidal anti-inflammatory drugs and triptans are first line treatment of a migraine attack. Nevertheless, when used in combination, these medications deliver a synergistic action. In this article, we review a combination of sumatriptan and naproxen sodium for the treatment of migraine headache as an underused treatment option in Lithuania.